Systematization of experiences in natural resource conservation and payment for ecosystem services at the Santa Isabel Micro-basin in Namasigue, Choluteca, Honduras. Guaranteeing the water supply for domestic use by the communities in the area of influence - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
6 pages